2002
DOI: 10.1046/j.1365-4362.2002.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting zinc as an important antioxidant for skin

Abstract: Antioxidants play a critical role in keeping skin healthy. The antioxidant benefits of vitamin C and E are well known, but the importance of the trace mineral, zinc, has been overlooked. This article reviews the evidence supporting zinc's antioxidant role in protecting against free radical-induced oxidative damage. Zinc protects against UV radiation, enhances wound healing, contributes to immune and neuropsychiatric functions, and decreases the relative risk of cancer and cardiovascular disease. All body tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(159 citation statements)
references
References 49 publications
6
145
0
8
Order By: Relevance
“…It is a major antioxidant trace element through zinc-induced metallothionein synthesis (Bell and Vallee, 2009), Zn-Cu superoxide dismutase, competition with iron and copper in Fenton's reaction and thiol group protection (Powell, 2000). Zinc has important roles particularly in the physiopathology of eye (Grahn et al, 2001;Ugarte and Osborne, 2001), skin (Rostan et al, 2002;Lansdown et al, 2007), bone (Peretz et al, 2001;Palacios, 2006) and brain (Takeda, 2001;Frazzini et al, 2006). Zinc is also crucial for immunity (Fraker and King, 2004;Haase and Rink, 2009) and hormonal excretions.…”
Section: Introductionmentioning
confidence: 99%
“…It is a major antioxidant trace element through zinc-induced metallothionein synthesis (Bell and Vallee, 2009), Zn-Cu superoxide dismutase, competition with iron and copper in Fenton's reaction and thiol group protection (Powell, 2000). Zinc has important roles particularly in the physiopathology of eye (Grahn et al, 2001;Ugarte and Osborne, 2001), skin (Rostan et al, 2002;Lansdown et al, 2007), bone (Peretz et al, 2001;Palacios, 2006) and brain (Takeda, 2001;Frazzini et al, 2006). Zinc is also crucial for immunity (Fraker and King, 2004;Haase and Rink, 2009) and hormonal excretions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the essential trace metals, zinc is an important element of more than 200 metalloenzymes, including the antioxidant superoxide dismutase (SOD) enzyme (3). In the cardiovascular system, zinc deficiency impairs the integrity of the endothelial cells (4) while favoring lipid peroxidation by enhancing oxidative-stress (5) and therefore may play a critical role in atherogenesis (6).…”
Section: Introductionmentioning
confidence: 99%
“…The author also indicated that a numerical trend of improvement of WHC of breast meat was observed when birds fed various ratios of supplemental manganese versus zinc (Saenmahayak, 2007). Zinc act as an antioxidant (Rostan et al, 2002) that can reduce oxidation in the muscle tissue. Increased levels of oxidation can damage cell membranes, reducing their integrity and allowing seepage of intracellular fluids.…”
Section: Resultsmentioning
confidence: 99%